Design and Implementation of a Wastewater Heat Recovery System Prototype for Electric Showers in Quito-Ecuador - Remache-Vinueza, Byron (2020)
A wastewater heat recovery system was designed and implemented in the city of Quito - Ecuador. The prototype consists of adapting a heat exchanger to recover energy from wastewater and preheat the water that enters an electric shower. A temperature control system was designed and adapted to work based on a preset comfort temperature. A procedure for the manufacture of copper U-pipe fittings was developed for the construction of the heat exchanger coil, which consists of freezing water inside the pipe so that when rolled it avoids crushing and excessive loss of the inner diameter. Results show that for an average family of 4 members a reduction of energy consumption by 57% is possible. For the case of Ecuador, a reduction of 56.69 Mt of equivalent CO2 emissions was estimated if the system was implemented across the country. A payback period of 8.35 years was calculated for the initial investment. © 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.